PENGARUH BEBAN LALU LINTAS TERHADAP KERUSAKAN PADA RUAS JALAN TAMBUNAN-DURIN SERUGUN KECAMATAN SIBOLANGIT KABUPATEN DELI SERDANG (STUDI KASUS) - RONALDO BARUS; RIZKY FRANCHITIKA; KEVIN JOSUA GINTING (JURNAL ILMIAH MAKSITEK, 2023)
On the road section around Tambunan-Durin Serugun, Sibolangit sub-district, Deli Serdang is included in the Class IIIA primary collector road whose status belongs to the Regency. Over time, the components or structure of the road continue to experience hardening due to the load of various oil palm and quarry transport vehicles in the form of trucks that have the amount of excess pressure relative to the load capacity that the road should be able to accept. If this continues, the planned life of the road section will be shorter than it should be. The purpose of this evaluation is to analyze the impact felt by the road pavement structure due to the overloading of vehicles on it which can cause an increase in the axle load above the predetermined standard. The aim of the researchers in this study is to find out whether LHR (excessive load) can cause damage to the Tambunen-Durin Serugun road pavement using the ESAL method by calculating every change in the weight of the road structure to determine the planned age of the pavement. The results stated that the damage to the Tambunan-Durin Serugun road was caused by excessive load.